Let $f(x)$ be a ordinary generating function for the sequence $ \{\ a_0, a_1, a_2... \}\ $ Find the ordinary generating function for $b_0 = b_1 = 0, b_2 = 1$ $b_n = a_n$ for $n \geq 3$.

Also find the generating function for $b_n = 0$ for even $n$, $b_n = a_n$ for odd $n$.

My attempts

For the first problem, $A(x) = 0+0+1x^2+a_3x^3+a_4x^4...$

So $$g(x) = x^2 + \sum_{n=3}^\infty a_n x^n$$

$$\Rightarrow x^2 + \sum_{n=0}^\infty a_n x^{n+3}$$ $$ \Rightarrow x^2 + \sum_{n=0}^\infty a_n x^n \cdot x^{-3}$$ $$\Rightarrow x^2 + f(x) \cdot x^{-3}$$

For the next problem I've got the sequence to be: $$ \{\ 0,a_1 , 0 , a_2 , 0, a_3\ldots \}\ $$

So $$A(x) = \{\ a_1 x + a_3 x^3 + a_5 x^5 \ldots \}\ $$

Which implies $$g(x) = \sum_{n=0}^\infty a_n x^n - \sum_{n=0}^\infty a_{2n} x^n$$

$$g(x) = f(x) - \sum_{n=0}^\infty a_{2n} x^n$$

But I can't get further. I hope my progress so far is correct in these.

Thank you.

  • 2
    $\begingroup$ A word of advice: any time you write an identity of power series, it is a good idea to check and make sure the coefficients of $x^n$ are the same on both sides for small values of $n$. You'll likely spot your errors (pointed out by Alex) that way. (+1 for showing the work on your problem) $\endgroup$ Apr 2, 2014 at 19:12

2 Answers 2


So for the first one there are a couple of issues, when you go from summing from $n = 3$ to $n=0$ you add 3 on to the power, but not the index of the coefficient. Also when you factor out the $x^3$ it turns into $x^{-3}$. Fix these things and see how far you can get.

For the second I'd recommend looking at $f(-x)$ and comparing that to $f(x)$.

  • $\begingroup$ Do you mean I should write $$x^2 +\sum_{n=0}^\infty a_{n+3} x^n \cdot x^3$$? $\endgroup$
    – Paze
    Apr 2, 2014 at 19:11
  • $\begingroup$ Yeah that looks better to me. $\endgroup$ Apr 2, 2014 at 19:13
  • $\begingroup$ I can't get further with that one. I'm having troubles representing it as $f(x)$ now. I looked into $f(-x)$. How does $$f(x)+2 f(-x)$$ sound for an answer for the second problem? $\endgroup$
    – Paze
    Apr 2, 2014 at 19:25
  • $\begingroup$ That's definitely the right idea, as Micheal suggested, try it on a small example though, e.g. $f(x) = 1$. Yeah that first one is a little hard to represent with just $f(x)$ like terms, however using terms like $f(0)$ I think it should be possible though. $\endgroup$ Apr 2, 2014 at 19:32
  • $\begingroup$ I'm still stuck trying to represent it as $f(x)$. Can you hold my hand a bit on this one? $\endgroup$
    – Paze
    Apr 2, 2014 at 22:35

You have to get rid of the first terms, and add in the new ones: $$ f(z) - a_0 - a_1 z - a_2 z^2 + b_0 + b_1 z + b_2 z^2 $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.